Dynamics of circulating vascular endothelial growth factor‐A predict benefit from antiangiogenic cediranib in metastatic or recurrent cervical cancer patients. Issue 8 (13th April 2019) - Zhou, Cong; Taylor, Sarah; Tugwood, Jonathan; Simpson, Kathryn; Jayson, Gordon C.; Symonds, Paul; Paul, James; Davidson, Susan; Carty, Karen; McCartney, Elaine; Rai, Debbie; Dive, Caroline; et al.
Abstract : Aims: There is a need for predictive and surrogate response biomarkers to support treatment with antiangiogenic vascular endothelial growth factor (VEGF) inhibitors. We aimed to identify a minimally‐invasive biomarker predicting benefit from cediranib pretreatment or early during treatment in patients with recurrent or metastatic cervical cancer. Methods: Blood samples were collected before treatment, during treatment and upon disease progression where appropriate from patients enrolled in CIRCCa, a randomised phase II trial of carboplatin and paclitaxel with or without cediranib. Plasma concentrations of VEGF‐A, VEGF‐receptor 2, Ang1 and Tie2 were measured using multiplex enzyme‐linked immunosorbent assay. Pretreatment and temporal changes of the biomarkers were investigated using proportional hazard regression and unsupervised clustering analysis. Results: Samples ( n = 556) from 52 patients were analysed. VEGF‐receptor 2 ( P = .0006) and Tie2 ( P = .04) were downregulated following cediranib, while VEGF‐A ( P = .0025) was upregulated. High Eastern Cooperative Oncology Group performance status ( P = .02, hazard ratio [HR] = 2.15, 95% confidence interval [CI] 1.13–4.09) and low pretreatment Tie2 concentrations ( P = .003, HR = 0.57, 95%CI 0.39–0.83) were independent prognostic factors associated with reduced progression‐free survival. Two patterns of changes in VEGF‐A following cediranib were identified. Patients with elevated VEGF‐A in the first 3 treatment cycles, regardless of magnitude, had reduced progression‐free survival in the placebo arm but improved survival with the addition of cediranib ( P = .019, HR = 0.13, 95% CI 0.02–0.71). Conclusion: Patterns of early elevation in plasma VEGF‐A should be studied further as a potential biomarker to predict treatment benefit from cediranib.